DISPERSION EQUATION FOR PLASMA WAVE PROPAGATION AT THE INTERFACE OF A STOCHASTIC ENVINRONMENT - MARCU, A.; MOCANU, G. (Studia Universitatis Babeș-Bolyai Physica, 2018)
The present paper investigates the effect of a stochastic term in the equation of motion in the MHD approximation. The end purpose is to find whether or not, for the case of an interface between two media of different physical properties, the stability behavior of the waves characteristic to the interface changes. Our results show that, for a certain parameter set, the stability behavior does change: namely a configuration which is stable in the deterministic approach may become unstable when stochastic effects are considered.